Religion of Islam and Microfinance: Does It Make Any Difference? - Mobin, M.A. (Routledge, 2017)
This study is the initial attempt to investigate first whether microfinance institutions (MFIs) perform differently in the OIC countries where Islam is the prevailing religion and second, how Islamic microfinance institutions are different (if any) from the conventional MFIs. To accomplish these objectives, we employ a dynamic difference and system-generalized method of moments estimators. Our findings tend to indicate that there are significant differences in the way Islamic MFIs performed and operated as compared to that of the conventional MFIs in certain regions. However, in other regions, there were no significant differences in operation and performance between the Islamic MFIs and Conventional MFIs. The study presents important insights for the Islamic microfinance managers and donors as well as the policy makers. Copyright © Taylor & Francis Group, LLC.